Development of Evaluation Systems – Evaluation Capacity Building in the Framework of the New Challenges of EU Structural Policy - Silke N. Haarich; Jaime del Castillo Hermosa (European Regional Science Association (ERSA), 2004)
The paper presents the changing role of evaluation for public policies and the increasing importance of comprehensive evaluation systems for more effective and learning public institutions. In this context, evaluation systems are becoming an essential element of governance and democratic processes. Within the framework of the current EU Structural Policy and its new challenges (enlargement, new priorities, regional policy paradigm), the creation and the development of evaluation capacities and comprehensive evaluation systems becomes increasingly an instrument for organizational learning and policy improvement. In this context, the development of evaluation systems is not only fundamental for the new member states, but also for countries with a poor evaluation culture or a fragmented evaluation system. However, evaluation still lacks the necessary resources and infrastructure to become an accepted and integrated governance tool, despite the growth of the European Evaluation Community and the take-off of several National Evaluation Societies in the past years. Unexploited potentials exist on the supply side (evaluators, skills, training, dialogue), but also on the demand side (commissioning, data monitoring, use of evaluations) of the evaluation system. Evaluation Capacity Building (ECB), as an approach for the development of evaluation systems, is the integrated and planned development of skills, resources and infrastructures and the intentional shift towards an evaluation culture in an organization, department or government. Nonetheless, getting to grips with the institutionalisation of the discipline of evaluation and the building of an ongoing evaluation capacity turns out to be extremely difficult: Which are concrete measures of ECB? Who is responsible for the measures, for the implementation? What are the target groups? When has the ECB been successful? are only some of the questions that come up.
Keywords: 330